2013
DOI: 10.1186/1471-2377-13-54
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid neurofilament light chain protein levels in subtypes of frontotemporal dementia

Abstract: BackgroundFrontotemporal dementia (FTD) is recognised as a clinically and morphologically heterogeneous group of interrelated neurodegenerative conditions. One of the subtypes within this disease spectrum is the behavioural variant FTD (bvFTD). This is known to be a varied disorder with a mixture of tau-positive and tau-negative underlying pathologies. The other subtypes include semantic dementia (SD), which generally exhibits tau-negative pathology, and progressive non-fluent aphasia (PNFA), which is usually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
69
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 111 publications
(82 citation statements)
references
References 31 publications
11
69
2
Order By: Relevance
“…NfL is released from damaged neurons. Concentrations in CSF are increased in people with neurodegenerative diseases, including Alzheimer's disease, 13 amyotrophic lateral sclerosis, 13 and frontotemporal dementia 13, 14. Four small-scale cross-sectional studies found raised concentrations of NfL in the CSF of individuals with Huntington's disease,8, 15, 16, 17 and we have shown a close association between increased concentrations of NfL and mHTT in CSF 8 …”
Section: Introductionsupporting
confidence: 60%
“…NfL is released from damaged neurons. Concentrations in CSF are increased in people with neurodegenerative diseases, including Alzheimer's disease, 13 amyotrophic lateral sclerosis, 13 and frontotemporal dementia 13, 14. Four small-scale cross-sectional studies found raised concentrations of NfL in the CSF of individuals with Huntington's disease,8, 15, 16, 17 and we have shown a close association between increased concentrations of NfL and mHTT in CSF 8 …”
Section: Introductionsupporting
confidence: 60%
“…This result is similar to another recent study of CSF NfL that demonstrated similar elevations in CSF NfL in SD. 39 Together, these data suggest that CSF NfL may be more prominently elevated in individuals with SD than other FTD subgroups. Whether these elevations reflect the association of SD with FTLD-TDP pathology, 40 or some other component of SD biology will require further study in a larger cohort of autopsy-confirmed cases.…”
Section: Discussionmentioning
confidence: 78%
“…This is unfortunate as MND mimics often display relatively low concentrations of CSF NFL . Also in FTD there are subtypes, such as progressive non-fluent aphasia, that do not have as markedly elevated CSF concentrations (Landqvist Waldö et al, 2013), as the common FTD variants. However, the main hypotheses of this study were clearly confirmed even though the influence of these subgroups might have hampered it.…”
Section: Discussionmentioning
confidence: 99%